Shareholder-driven corporate governance - Anand, Anita, 1967- (Oxford scholarship online., 2021)
This is a text about the ways in which capital markets have come to be shaped by the ubiquity of sophisticated investors. In particular, many of today's investors have the economic might & technical capacity to play a role in the decision-making of the corporations in which they invest. This phenomenon brings with it a host of benefits, such as mechanisms to ameliorate the moral hazard that can exist when the people who bear the risk of corporate activity are different from those who make decisions. A key element of this work is an examination of the ways in which thinking about corporations & capital markets must change to reflect the prevalence of sophisticated shareholders. The book develops a concept - shareholder-driven corporate governance - to explain the role of powerful shareholders & to propose a regulatory scheme that furthers their participation in corporate decision-making.